Musical Qualia : Using the Concept of Bellezza to Characterize Musical Experience - Hermus, Nathan J (My University, 2015)
Affective musical experience in response to chosen music was investigated in order to explore musical qualia, using Wicklund and Vida-Grim's (2004) concept of bellezza to guide predictions. It was hypothesized that during an aesthetic response characterized by bellezza music listeners would experience openness to multiple sensory dimensions, absorption in the experience, desire to continue, and transformation of time. In order to create a state of bellezza, participants (N = 91) were asked to choose a song to listen to, which they felt they could "just keep listening to" for its own sake. Then, half of the participants were randomly assigned to one of two experimental conditions, in which bellezza was either induced through music listening or inhibited by a hunger salience manipulation that accompanied the music listening. Manipulation checks revealed that the hunger salience manipulation was not strong enough, and hypotheses concerning attentional breadth, desire to continue, and transformation of time were not supported; the results concerning absorption was only trending toward significance. There were also two non-significant trends indicating that participants in the bellezza condition were more likely to use metaphors in their drawings to represent what they had experienced during music listening and that they were more likely to take the perspective of the song writer or song character compared to those in the bellezza inhibited condition. Exploratory post-hoc analyses revealed significant effects on the "loss of self-consciousness" subscale of Jackson and Marsh's (1996) Flow State Scale, a non-significant trend toward a difference in goal orientation between conditions, and a significant interaction effect showing participants in each condition rated different musical characteristics as most important to their enjoyment of the music.
A Thesis Submitted in Partial Fulfillment of the Requirements for the Degree of Master of Science- Psychology Cognitive Affective
Keywords: Music; Cognitive theory; Emotions in music; Psychological aspects of music